Genome-wide analysis of WRKY gene family and the dynamic responses of key WRKY genes involved in cadmium stress in Brassica juncea - Li, Shaocui; Ji, Qingqing; An, Xia; Chen, Changli; Luo, Xiahong; Liu, Tingting; Zou, Lina (Frontiers in Plant Science, 2024)
The WRKY transcription factors comprise one of the most extensive gene families and serve as pivotal regulators of plant responses to heavy metal stress. They contribute significantly to maintaining plant growth and development by enhancing plant tolerance. However, research on the role of WRKY genes in response to cadmium (Cd) stress in mustard is minimal. In this study, we conducted a genome-wide analysis of the mustard WRKY gene family using bioinformatics. The results revealed that 291 WRKY putative genes (BjuWRKYs) were identified in the mustard genome. These genes were categorized into seven subgroups (I, IIa-e and III) through phylogenetic analysis, with differences in motif composition between each subgroup. Homology analysis indicated that 31.62% of the genes originated from tandem duplication events. Promoter analysis revealed an abundance of abiotic stress-related elements and hormone-related elements within the BjuWRKY genes. Transcriptome analysis demonstrated that most BjuWRKY genes exhibited differential expression patterns at different Cd treatment stages in mustard. Furthermore, 10 BjuWRKY genes were confirmed to respond to Cd stress through the construction of a BjuWRKY protein interaction network, prediction of hub genes, and real-time fluorescence quantitative PCR analysis, indicating their potential involvement in Cd stress. Our findings provide a comprehensive insight into the WRKY gene family in mustard and establish a foundation for further studies of the functional roles of BjuWRKY genes in Cd stress response.